Hemothorax Occurring After Central Venous Catheter Removal: A Case Report - Dib, Jony; Boutari, Rim; Yaacoub, Boshra; Al Khalil, Nayef; Al Ayoubi, Mohamad; Itani, Othman (International Journal of Clinical Research, 2022)
Background: Central venous catheterizations are used frequently in critical care unit. The procedure is associated with various complications ranging from mechanical ones during insertion and the possibility of vessel laceration and dissection to infections, not to forget haemothorax and pneumothorax that may require chest tube insertion. However, some complications may also origin from its removal. Case Report: This is a case of a 72-year-old patient with multiple comorbidities admitted to the Intensive Care Unit (ICU) for respiratory distress. A central line was inserted because a peripheral line was hard to establish, and as a consequence of catheter removal, he had a massive right-sided hemothorax. Conclusion: Central venous line removal could cause fatal complications such as massive hemothorax that should be looked for. We emphasize monitoring of patients after catheter removal because the uncommon nature of this complication can lead to diagnosis delay and even misdiagnosis.